Heat transfer of thin-film Casson hybrid nanofluid flow across an unsteady stretching sheet - Nur Ilyana Kamis; Md Faisal Md Basir; Taufiq Khairi Ahmad Khairuddin; Lim Yeou Jiann (Annals of Mathematical Modeling, 2021)
Hybrid nanoparticles copper andalumina effect on the heat transfer of thin-filmblood flow toward an unsteady permeablestretching sheet is studied. The influence ofsuction is considered. The governing partialdifferential equations together with boundaryconditions are reduced into the set of ordinarydifferential equations by implementing thesimilarity transformations. The Keller-boxmethod is used to solve the momentum and heatequations. The characteristics of the blood flowand heat transfer under the effect ofunsteadiness parameter, nanoparticles volumefraction, Casson parameter, and intensity ofsuction for different thin-film thickness arediscussed. The numerical results of the velocityand temperature profiles are graphicallydisplayed. The physical interest such as thelocal skin friction and Nusselt number aredepicted in a tabular form.